Circuito espacial de produção de sal:o uso do território do município de Macau/RN pelas indústrias salineiras - Maia, Manuel Thiago de Araújo (2011)
The current work it is a research of the spatial circle of salt production and the uses implied by RN salt industry, specifically the city of Macau / RN. Part of the issue - how it gives the uses implied by the spatial distribution of salt in the current historical period, known by some geographers as technical-scientific-informational. The way taken to answer this research was through readings of researches already carried out, field research in government agencies, the use of photographs, questionnaires and interviews. The search for data on production salting, their handling and marketing was one of the methodology steps. The result of this research was the perception of the dynamic activity of salting and uses transmitted within the city of Macau / RN, and the state of Rio Grande do Norte.